Strategi Implementasi Model Kurikulum Agama dan Kurikulum Dinas pada Pembelajaran Pendidikan Agama Islam - Muhamad ibnu Malik; Erihadiana, Mohamad; Muslih, Hafid (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
The aim of this research is to determine strategies for implementing religious curricula and official curricula in Islamic religious education learning, their effectiveness as well as supporting and limiting factors in the implementation of these curricula. The method used by researchers is a qualitative method with a descriptive approach, the type of research applied is a case study. This research was conducted at SMPIT Anni'mah Bandung Regency. The research results show that the curriculum model design strategy applied in Islamic religious education learning is the religious curriculum model and the service curriculum. The effectiveness of implementing the religious curriculum model and service curriculum is supported by several activity programs. As for the supporting and inhibiting factors for implementing this curriculum model, which were obtained internally, students were found to be late and lack motivation. External factors were applications that experienced errors in the learning process.